STUDY ON FATIGUE PERFORMANCE OF CRACKED STEEL STRUCTURE REPAIRED WITH STOP-HOLE AND CFRP - HUANG ChuanHai; LIU ZhiPing (Jixie qiangdu)
For crane metal constructions,fatigue cracks during long-term services easily occurs. A combination of crack stop-hole and CFRP for repairing cracked metal structures can achieve better results than single repairing methods. For the crack initiation stage of the crack stop-hole edge after composite repair,by utilizing ABAQUS and FE-SAFE to establish a finite element analysis model,the influence of factors such as the reinforcement method,the radius of the stop-hole,the length of the fatigue crack and the distance from the crack tip to the edge of the crack stop on the crack initiation life were analyzed and verified through experiments. The results show that it is feasible to use ABAQUS and FE-SAFE to analyze the durability of the composite repaired structure,which can provide references for the formulation of plans to repair.